Regulation of plasma agouti-related protein and its relationship with hunger in lean and obese men. (1st December 2016) - Hazell, Tom J.; Sawula, Laura; Edgett, Brittany A.; Walsh, Jeremy J.; Gurd, Brendon J.
Abstract: Agouti-related protein (AgRP) is an orexigenic (appetite stimulating) neuropeptide suggested to exert tonic control over long-term energy balance. While some have speculated AgRP is not involved in the episodic (i.e. meal to meal energy intake) control, acute decreases in plasma agouti-related protein (AgRP) following a meal have been observed in humans in a role consistent with episodic control for AgRP. Whether changes in plasma AgRP are associated with episodic, and/or tonic changes in appetite has yet to be directly examined. The present study examined the relationship between agouti-related protein (AgRP), leptin and the regulation of appetite following a 48-h fast and an acute meal challenge. Blood samples were obtained from young lean and obese men before and after a 48 h fast (lean n = 10; obese n = 7). Fasting resulted in an increase in AgRP and a decrease in leptin with these changes being greater in lean than obese. In addition, blood samples were obtained from lean men before and 1, 2, 3 and 4 h after a meal (n = 8). Following a meal, AgRP was reduced from 2 to 4 h, a change that was dissociated from both leptin and subjective measures of hunger and satiety. These results demonstrate that AgRP is not associated with changes in hunger or satiety, and can change without corresponding changes in leptin. This suggests that AgRP may not be involved in the episodic control of appetite and the release of AgRP may involve signals other than leptin.